Concomitant using of topical carrageenan-kappa and oral vitamin D against 7, 12-dimethylbenz[a]anthracene induced-oral cancer in rats: A synergism or an antagonism effects - Ali, Aseel J; Al-Juboori, Jamal N.A.; Al-Nimer, Marwan (Brazilian Dental Science, 2020)
Objective: ?-carrageenan is a food stabilizer agent which has an antiproliferative effect, while vitamin D is a prohormone acts on the nuclear receptor and has a cytotoxic against cancer. This study aimed to show the synergistic effect of using topical ?-carrageenan and oral administration of the vitamin D on the 7, 12-dimethylbenz[a] anthracene (DMBA)-induced oral cancer. Material and Methods: fifty four male albino rats were randomly divided into seven groups: Acetone-treated served as control (Group I), vitamin D (5000UI)-treated (Group II), ?-carrageenan (1%)- treated (Group III), DMBA (0.5%)-treated (Group IV), Acetone, ?-carrageenan and DMBA were administered topically on both cheeks and palate, five times weekly for 12 weeks, while the vitamin D was  administered orally twice weekly for 12 weeks. Groups V, VI, and VII were animals treated with vitamin D, ?-carrageenan, and both vitamin D and ?-carrageenan for 8 weeks after induction of oral cancer. At the end of the study, blood samples were obtained by cardiac puncture for determination of TNF-? and EGFR. Results: In the groups III and IV, serum EGFR showed significant low levels compared with Group I. In the Group VII, serum EGFR showed a significantly (p=0.014) low level compared with Group IV (614.3±69.7 pg/ml versus 882.4±45.6 pg/ml, respectively). Higher percentages of high levels of TNF-? were observed in the Groups VI and VII, while a lower percentage of EGFR was observed in the Group VI. Conclusion: both ?-carrageenan and vitamin D have antiproliferative effect against DMBA-inducing oral cancer by increasing the levels of TNF-? and suppressing the signaling pathway of EGFR. Concomitant using ?-carrageenan and vitamin D reduces the antiproliferative effect of each other. KeywordsOral cancer; 7, 12-dimethylbenz[a] anthracene; Vitamin D; ?-carrageenan; Epidermal growth factor receptor; Tumor necrosis factor-?.